Identification Of Salmonella Enterica Subspecies Enterica Serovar Typhi-Specific Genes For The Development Of Dna-Based And Antibody-Based Diagnostics For Typhoid Fever - Goay , Yuan Xin (2018)

(untitled)
Typhoid fever is caused by Salmonella enterica subspecies enterica serovar Typhi (S. Typhi). It is an acute systemic disease which remains a major public health burden worldwide. A lack of specific and sensitive diagnostic markers for detection of S. Typhi at single-gene target resolution prevents effective diagnosis and therefore efficient control of the disease. In the first phase of this study, genome level comparison of S. Typhi with other enteric pathogens was performed using BLASTn. Six genes, i.e. STY0201, STY0307, STY0322, STY0326, STY2020 and STY2021 were found to be specific and sensitive in silico. Six individual single-gene target PCR assays with the incorporation of an internal amplification control (IAC) were developed and optimised using Taguchi method.